Association of telomere length in peripheral leukocytes with chronic hepatitis B and hepatocellular carcinoma. Issue 39 (September 2016) - Ma, Qiang; Cai, Jiajing; Cai, Yan; Xu, Yuan; Chang, Fan; Xu, Lei; Zhang, Guoyuan; Guo, Xiaolan
Abstract: Background & Objectives: Telomere plays a critical role in the maintenance of genomic stability in eukaryotic chromosomes. More and more findings have shown that alteration in telomere length may involve in normal somatic cells and some diseases, however, whether the telomere length is associated with the development and/or progression of hepatic diseases remains poorly understood. Methods: A case–control study was employed to illustrate the correlation of relative telomere length (RTL) with chronic hepatitis B (CHB) and hepatocellular carcinoma (HCC). In this study, 152 patients with HCC, 212 patients with CHB, and 184 healthy controls were recruited. Genomic deoxyribonucleic acid (DNA) was extracted from the peripheral blood leukocytes, and fluorescence quantitative polymerase chain reaction (FQ-PCR) was used to detect telomere repeated numbers and 36B4 copy numbers. The RTL was calculated by telomere repeat copy number to single-copy gene number ratio in each sample compared with a reference DNA sample. Results: We found that the RTL in HCC group was the longest, followed by CHB group, and healthy control group was the shortest, showing significant statistical differences. When participants were categorized into longer and shorter group according to medium value in healthy controls, individuals who had longer RTL had a significant increased risk of CHB (odds ratio [OR]: 1.83, 95% confidence interval [CI]: 1.22–2.73) when the healthy control was used as the reference groups; furthermore, longer RTL also showed higher incidence of HCC (OR: 3.22, 95% CI: 2.01–5.17; OR: 1.58, 95% CI:1.03–2.41) when healthy control and CHB were used as the reference groups, respectively. When participants were categorized further into 4 groups according to quartile values of RTL in healthy controls, it showed that the longest RTL was also associated with an increased risk of CHB (OR: 2.09, 95% CI: 1.17–3.74) and HCC (OR: 4.31, 95% CI: 2.18–8.52; OR: 2.86, 95% CI: 1.53–5.34) when control and control/CHB group were used as the reference groups, respectively. Conclusion: Our results suggest that the alteration of telomere length in peripheral leukocytes might be involved in the hepatitis B virus infection and HCC events, and RTL might be a potential useful predictor of CHB and HCC.